A tracer-based inversion method for diagnosing eddy-induced diffusivity and advection. (February 2015) - Bachman, S.D.; Fox-Kemper, B.; Bryan, F.O.
Highlights: A multiple-tracers diagnosis method can describe the full eddy transport tensorR . Overdetermination of the linear flux-gradient relationship improves accuracy in diagnosingR . Practical guidelines for using this inversion method are introduced. Nonconservative effects (i.e. tracer restoring) can be corrected using a modified flux-gradient relation. Advective and diffusive transport can be isolated with this method – rotational and divergent cannot. Abstract: A diagnosis method is presented which inverts a set of tracer flux statistics into an eddy-induced transport intended to apply for all tracers. The underlying assumption is that a linear flux-gradient relationship describes eddy-induced tracer transport, but a full tensor coefficient is assumed rather than a scalar coefficient which allows for down-gradient and skew transports. Thus, Lagrangian advection and anisotropic diffusion not necessarily aligned with the tracer gradient can be diagnosed. In this method, multiple passive tracers are initialized in an eddy-resolving flow simulation. Their spatially-averaged gradients form a matrix, where the gradient of each tracer is assumed to satisfy an identical flux-gradient relationship. The resulting linear system, which is overdetermined when using more than three tracers, is then solved to obtain an eddy transport tensor R which describes the eddy advection (antisymmetric part of R ) and potentially anisotropic diffusion (symmetric part of R ) in terms of coarse-grained variables. The mathematical basis for this inversion method is presented here, along with practical guidelines for its implementation. We present recommendations for initialization of the passive tracers, maintaining the required misalignment of the tracer gradients, correcting for nonconservative effects, and quantifying the error in the diagnosed transport tensor. A method is proposed to find unique, tracer-independent, distinct rotational and divergent Lagrangian transport operators, but the results indicate that these operators are not meaningfully relatable to tracer-independent eddy advection or diffusion. With the optimal method of diagnosis, the diagnosed transport tensor is capable of predicting the fluxes of other tracers that are withheld from the diagnosis, including even active tracers such as buoyancy, such that relative errors of 14% or less are found.